Customer switching behavior among Indonesian Muslims: Evidence from the merger of Indonesia's State-owned Islamic banks - Mochlasin Mochlasin; Nornajihah Nadia Hasbullah; Ahmad Mifdlol Muthohar; Saiful Anwar (Cogent Business & Management, 2023)
This research examined the factors that affect customer satisfaction and switching behavior in the post-merger of the state-owned Islamic banks in Indonesia. Data were collected by distributing an online questionnaire to a total of 210 Muslim customers. Furthermore, the collected data were analyzed using SEM-PLS. The findings indicate that product quality can enhance customer satisfaction, and service quality can mitigate customer switching behavior. Interestingly, the Shariah compliance also has a significant effect on customer satisfaction and switching behavior by Indonesian Muslim. This suggested that, in Indonesia, where the majority of the population is Muslim, businesses that prioritize Shariah compliance are more likely to retain customers. Implication of this research provides empirical evidence to Islamic banks regarding the significance of reputation. Based on the findings, bank management tends to consider to integrate the product quality, service quality, and Shariah compliance into the banking business model. It is essential to consistently apply Sharia compliance to enhance customer satisfaction and reduce switching behavior. The Originality of this research is the first in Indonesia to examine customers' switching behavior in the context of the merger of the State-Owned Islamic Banks. The findings can serve as an evaluation tool for the government and Islamic bank management to strengthen the country's economy.
Keywords: 650; customer satisfaction; customer switching behavior; product quality; service quality; sharia compliance; technological sophistication